2020
DOI: 10.1111/ijlh.13303
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 patient with immune thrombocytopenic purpura

Abstract: Immune thrombocytopenic purpura (ITP) is an acquired disease characterized by thrombocytopenia secondary to autoantibodies against platelet antigens. Secondary ITP is common after viral infections 1. We here report a case of ITP in a patient with COVID-19 pneumonia. An 89-year-old man with congestive heart failure, essential hypertension, type 2 diabetes, chronic kidney disease, and atrial fibrillation on anticoagulation (AC) presented to the emergency department in March 2020 with a 3-day history of shortness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…After the search, 32 articles with a total of 56 cases were selected. 132 Our own patient was also included in the final analysis, so 57 cases were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…After the search, 32 articles with a total of 56 cases were selected. 132 Our own patient was also included in the final analysis, so 57 cases were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…In the study population, 26 patients had complete response and 8 patients showed only response to treatment according to study definition. A total of 3 individuals expired: one was due to intracranial hemorrhage [11] and others succumbed to severity of COVID-19 illness after showing platelet response to treatment [15,27]. A total of 4 patients (9%) had relapse following treatment response in the followup period [13,14].…”
Section: Treatment and Clinical Outcomesmentioning
confidence: 99%
“…Case reports and case series of ITP induced by COVID-19 have been reported in the literature, and multiple treatment protocols have been suggested. [3][4][5] Here, we report the clinical manifestations, mortality rate, and management of all COVID-19 patients admitted to the hospital and diagnosed with secondary ITP.…”
Section: Introductionmentioning
confidence: 99%